ANALYSING PRESUPPOSITION: A STUDY ON PRESIDENT AKUFO-ADDO’S STATE OF THE NATION ADDRESS (SONA), 2022 - Gyimah Manu, James; Ampong, Bernard; Marfo, Charles Ofosu (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
Presupposition can be said to be an assumption of a speaker prior to making an utterance or an implied claim of an utterance. Using qualitative method, the researchers examined various language structures that give rise to presuppositions. This was pursued by exploring the State of the Nation Address (SONA) delivered by President Akufo-Addo of Ghana on 30th March 2022. The analysis of the SONA, as the data of the study, revealed the utilization of a number of presupposition triggers – such as possessive construction, “one” construction, definite noun phrase, adverbial clause, relative clause, “even” construction, iteratives, change of state verbs, and factive verbs or phrases – under the existential, structural and lexical presuppositions. The article thus opines that the enactment of presuppositions, through the identified forms, affords the President the opportunity to disseminate his message with a higher degree of veracity on the conditions and happenings of the Ghanaian state.